Value propositions: A service ecosystems perspective. (September 2014) - Frow, Pennie; McColl-Kennedy, Janet R.; Hilton, Toni; Davidson, Anthony; Payne, Adrian; Brozovic, Danilo
Despite significant interest in value propositions, there is limited agreement about their nature and role. Moreover, there is little understanding of their application to today's increasingly interconnected and networked world. The purpose of this article is to explore the nature of value propositions, extending prior conceptualisations by taking a service ecosystem perspective. Following a critical review of the extant literature in service science on value propositions, value co-creation, service-dominant logic and networks and drawing on six metaphors that provide insights into the nature of value propositions, we develop a new conceptualisation. The role of value propositions is then explored in terms of resource offerings between actors within micro, meso and macro levels of service ecosystems. We illustrate these perspectives with two real-world exemplars. We describe the role of value propositions in an ecosystem as a shaper of resource offerings. Finally, we provide five key premises and outline a research agenda.